Pengaruh Pendidikan Kewirausahaan Dan Peran Orang Tua Terhadap Minat Berwirausaha Mahasiswa Prodi Pendidikan Ekonomi Semester IV Universitas Hamzanwadi Tahun Akademik 2023/2024 - Sari, Desi Purnama; Susilawati, Susilawati (Alpatih Harapan Semesta, 2024)
The purpose of this study was to determine the effect of Entrepreneurship Education and the Role of Parents partially or simultaneously on the entrepreneurial interest of Economic Education Study Program Students Semester IV, Hamzanwadi University, Academic Year 2023/2024. Entrepreneurship can be one of the preferences of students after graduating, students can create new jobs with the knowledge they have gained during college and supported by the role of parents. the method used is quantitative correlation, the research sample was 60 students of the Economic Education Study Program semester IV and the data collection method used a questionnaire. data analysis using multiple linear regression, determination test (R2) and hypothesis testing with partial test (T), simultaneous test (F). The results of the study indicate that Entrepreneurship Education and the Role of Parents have a Positive and Significant Effect Partially and Simultaneously on the Entrepreneurial Interest of Economic Education Study Program Students Semester IV, Hamzanwadi University, Academic Year 2023/2024. the coefficient of determination (R2) value of 0.515 means that 51.5% of the Entrepreneurship Education and Parental Role variables are able to explain the variable of students' interest in entrepreneurship.